Nonlinear Pricing and Exclusion: II. Must-Stock Products - Philippe Choné; Laurent Linnemer (Center for Economic Studies and ifo Institute (CESifo), 2014)
We adapt the exclusion model of Choné and Linnemer (2014) to reflect the notion that dominant firms are unavoidable trading partners. In particular, we introduce the share of the buyer's demand that can be addressed by the rival as a new dimension of uncertainty. Nonlinear price-quantity schedules allow the dominant firm to adjust the competitive pressure placed on the rival to the size of the contestable demand, and to distort the rival supply at both the extensive and intensive margins. When disposal costs are sufficiently large, this adjustment may yield highly nonlinear and locally decreasing schedules, such as retroactive rebates .
Keywords: L12; L42; D82; D86; 330; inefficient exclusion; buyer opportunism; disposal costs; quantity rebates; incomplete information